A longitudinal examination of the psychoeducational, neurocognitive, and psychiatric functioning in children with 22q11.2 deletion syndrome - Hooper, Stephen R.; Curtiss, Kathleen; Schoch, Kelly; Keshavan, Matcheri S.; Allen, Andrew; Shashi, Vandana (Research in developmental disabilities, 2013)
► Children with 22q11DS and controls underwent two neurocognitive and psychiatric evaluations 3.5 years apart. ► Significant cognitive deficits and higher incidence of psychiatric manifestations seen in 22q11DS children relative to controls at both T1 and T2. ► Slowed growth in attention, increased psychiatric symptoms and prodromal signs, and decreased GAF over time noted in 22q11DS children. ► T1 predictors of psychopathology at T2 included full-scale IQ and social-behavioral problems. The present study sought to examine the longitudinal psychoeducational, neurocognitive, and psychiatric outcomes of children and adolescents with chromosome 22q11.2 deletion syndrome (22q11DS), a population with a high incidence of major psychiatric illnesses appearing in late adolescence/early adulthood. Little is known of the developmental changes that occur in the early teen years, prior to the age of highest psychosis risk. Data were collected from 71 participants (42 subjects with 22q11DS and 29 control subjects) at Time 1 (T1) and Time 2 (T2), approximately 3.5 years later. The 22q11DS group was significantly lower functioning than controls on IQ, neurocognition, and academic achievement at both T1 and T2. Children with 22q11DS also showed significantly greater social-behavioral difficulties and psychiatric symptoms, and were more likely to meet criteria for psychiatric disorders at both time points. In evaluating change over time from T1 to T2, the 22q11DS group did not show significant changes in psychoeducational or psychiatric outcomes relative to the controls, however, lack of expected age-related gains in attention regulation were noted. Within the 22q11DS group, an increase in the Attenuated Prodrome for Schizophrenia (number of psychiatric symptoms) was noted from T1 to T2 and four children with 22q11DS met criteria for Psychosis for the first time. Predictors at T1 that uncovered psychopathology symptoms at T2 included full-scale IQ, externalizing symptoms, and problem social behaviors. Overall, younger adolescent and preadolescent children with 22q11DS in this study exhibited slowed growth in attention regulation, with an increase in subclinical symptoms of schizophrenia, suggestive of increasing impairments in domains that are relevant to the high risk of Schizophrenia. Early predictors of later psychopathology included both cognitive and behavioral abnormalities. These findings begin to elucidate the trajectory of changes in psychopathology in children with 22q11DS in the years leading up to the onset of major psychiatric illnesses.